Kristendom og hellenisme - en skæbnesvanger konstruktion - Klostergaard Petersen, Anders (Religionsvidenskabeligt tidsskrift, 2002)
This essay - representing an elaborated version of the author's inaugural lecture as an associate professor at the Department of the Study of Religion - is a critical survey of the classical scholarly discussion of Hellenism that particularly focuses on the Judaism-Hellenism dichotomy. By an exposition of the intellectual history of the background to the debate (notably Droysen), the author argues that the discussion has to a great extent been subject to the influence of a perceptual filter, representing a Christian apologietic concern - the scope of which is not fully recognised. Hellenism has served as a significant flottant capable of being attributed almost any meaning, but ultimately the category itself stems from a Christian concern, i.e. to construct a period serving as a legitimising cultural and religio-historical foilage for the appearance of early Christianity.Although some important cultural changes do occur subsequent to Alexander the Great (an increased tendency towards urbanisation, important military innovation, for example), they do not constitute tendencies that may be extended to include a universal sultural watershed common to the entire Mediterranean and extra-Mediterranian world and uniting it across the centuries. In addition to that, the discussion is suffering from a deficient interpretation of culture and identity. tghe meeting of different cultures and the confusions of different cultural traditions are perceived in terms of 'pure cultures'. Culture is ontologised or naturalised to the exten that a meeting of cultures is conceived of in terms of separate and fundamentally different cultures that are simultaneously understood to be internally homogenous. Each person is thought to be a carrier or container of his or her culture, thus for instance the Jew incarnating or representing Judaism in its entirelt. From this perspective divergent, modes of dultures are perceived in terms of cultural or religious contaminataion. Culture, however, does not exist - except as an abstraction - in such pure forms. It is per definition a messy affair.In conclusion I think that in future research we should refrain from using the category of Hellenism is the all-sweeping manner in which it has been used. In fact we should be very careful, when using Judaism, Hellenism or any other taxonomic abstraction, not to commit an 'ontological dumping', reifying concepts which exist only by virtue of scholarly categorisations. Rather than to continue to use a misunderstandable term and an ideologically biased category strongly dependent on a Christian perceptual filter, we should begin looking for the decisive innovations, the important cultural and religious changes, which at particular places and in specific periods may allow us to construe cultural watersheds.